2007
DOI: 10.1007/s00268-007-9110-7
|View full text |Cite
|
Sign up to set email alerts
|

Relations Among Circulating Monocytes, Dendritic Cells, and Bacterial Translocation in Patients With Intestinal Obstruction

Abstract: A significant inverse correlation was observed between the circulating monocyte count and the ratio of DCs among all cells in MLNs (r(2)= 0.259). Postoperative septic complications were 3.3 times more common in BT-positive patients than in BT-negative patients. A significant increase in the expression of DCs in MLNs was observed in patients with BT subsequent to intestinal obstruction. Our findings suggested that a low monocyte count (<290 /mm(3)) and the presence of preoperative SIRS might be useful factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
9
0
7
Order By: Relevance
“…Results from animal models and patient studies indicated that enteric bacterial overgrowth and microfloral ecological changes may contribute to the influx of enteric bacteria [4,8,25]. Abnormal epithelial permeability and downregulated immunity also played crucial roles in the mechanism of enhanced BT [5,16,26]. We and others showed that IO induced compartmentalized changes in mucosal histology, epithelial permeability and bacterial overgrowth, confined to the distal small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from animal models and patient studies indicated that enteric bacterial overgrowth and microfloral ecological changes may contribute to the influx of enteric bacteria [4,8,25]. Abnormal epithelial permeability and downregulated immunity also played crucial roles in the mechanism of enhanced BT [5,16,26]. We and others showed that IO induced compartmentalized changes in mucosal histology, epithelial permeability and bacterial overgrowth, confined to the distal small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mechanical bowel obstruction are of increased risk of septicemia which results in high rates of mortality [1,2]. The septic complications are associated with gut barrier dysfunction, and entry of gut microorganisms and bacterial products [4,5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Intestinal permeability changes are associated with higher BT levels and sepsis. 11,13 Local immune response and cytokines modulate intestinal permeability and BT to avoid increased inflammation. [14][15][16] Thus, the host immune response plays a major factor in the overall process.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of bacterial translocation (BT) leading to systemic sepsis has been supported by several experimental studies48 and some clinical studies,912 such as when the host is immunocompromised or critically ill. Conditions associated with splanchnic hypoperfusion, such as hemorrhagic shock and intestinal ischemia, result in the gut becoming a cytokine-generating organ, which is followed by intestinal mucosal injury and loss of gut-barrier function 13,14…”
Section: Introductionmentioning
confidence: 99%